2010
DOI: 10.1002/lt.22107
|View full text |Cite
|
Sign up to set email alerts
|

Successful outcomes following living donor liver transplantation for portopulmonary hypertension

Abstract: Pulmonary arterial hypertension (PAH) associated with portal hypertension [portopulmonary hypertension (PPHTN)] occurs in 2% to 10% of patients with advanced liver disease and carries a very poor prognosis without treatment. Most hepatic transplantation centers consider moderate to severe PPHTN to be a contraindication to liver transplantation because of the high rate of perioperative complications. We present 3 patients with PPHTN who were managed with intravenous prostacyclin therapy followed by living donor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 23 publications
0
27
0
1
Order By: Relevance
“…Initial experience indicated that post-transplant improvement in ''POPH'' was limited to patients with PH secondary to an increased cardiac output (elevated mean Ppa but PVR ,240 dyn?s?cm -5 ). Accumulating evidence from different transplant centres is now manifesting post-transplant improvement in selected POPH patients, some of them being able to wean-off their PAH-specific therapy a few months after LTx (probably ,50% of those surviving the early months after LTx) [33,40,54,56]. Although these are encouraging results, evidence derives from retrospective analyses of transplant databases or case series.…”
Section: Liver Transplantationmentioning
confidence: 99%
“…Initial experience indicated that post-transplant improvement in ''POPH'' was limited to patients with PH secondary to an increased cardiac output (elevated mean Ppa but PVR ,240 dyn?s?cm -5 ). Accumulating evidence from different transplant centres is now manifesting post-transplant improvement in selected POPH patients, some of them being able to wean-off their PAH-specific therapy a few months after LTx (probably ,50% of those surviving the early months after LTx) [33,40,54,56]. Although these are encouraging results, evidence derives from retrospective analyses of transplant databases or case series.…”
Section: Liver Transplantationmentioning
confidence: 99%
“…A mean PAP of 50 mmHg is contraindication to liver transplantation [3]. An aim of PAP of <35 mmHg is necessary if liver transplant is contemplated in cirrhotic patients [37]. The 5-year survival of POPH is 14-45% of those receiving medical treatment.…”
Section: Treatment Of Poph and Hps Are Different;mentioning
confidence: 99%
“…Assuming up to 8.5% of LT candidates have PPH, at any point in time there may be ∼1300 PPH-LT candidates [27]. The outcome of PPH following LT remains unpredictable despite screening, careful patient selection, higher priority for LT, and advances in single and combination PAH-specific therapies (Table 19.4) [69][70][71][72][73][74][75][76][77][78]. Current policy adopted by the American Association for the Study of Liver Diseases (AASLD) calls for screening TTE to detect pulmonary hypertension in every patient considered for LT in the United States [79].…”
Section: Liver Transplantationmentioning
confidence: 99%